2002
DOI: 10.1007/bf02573071
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase and tensin analog gene overexpression engenders cellular death in human malignant mesothelioma cells via inhibition of AKT phosphorylation

Abstract: Overexpression of PTEN engenders apoptosis in mesothelioma by AKT hypophosphorylation. The forced overexpression of PTEN may prove useful clinically in this treatment-resistant neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Regulation of Bcl2 by PTEN was on the transcriptional level and exogenous expression of Bcl2 was able to attenuate PTEN-induced chemosensitivity in LNCaP cells (Huang et al, 2001). Similar results have been observed in thyroid cancer cells, breast carcinoma cells and malignant mesothelioma cells (Ghosh et al, 1999;Weng et al, 2001a, c;Mohiuddin et al, 2002).…”
Section: Pten Signaling As a Lipid Phosphatasementioning
confidence: 53%
“…Regulation of Bcl2 by PTEN was on the transcriptional level and exogenous expression of Bcl2 was able to attenuate PTEN-induced chemosensitivity in LNCaP cells (Huang et al, 2001). Similar results have been observed in thyroid cancer cells, breast carcinoma cells and malignant mesothelioma cells (Ghosh et al, 1999;Weng et al, 2001a, c;Mohiuddin et al, 2002).…”
Section: Pten Signaling As a Lipid Phosphatasementioning
confidence: 53%
“…PI3K/Akt signalling pathway is negatively regulated by the tumour suppressor gene phosphatase and tensin homologue (PTEN). Over-expression of PTEN engenders apoptosis in MM by AKT hypophosphorylation [33]. In light of these facts it is possible to suppose that over-expression of PTEN could be the basis of hypophosphorylated Akt in the Ist-Mes-2 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification and mutation of PI3K and AKT genes have also been reported in several tumor types [88]. Although at present mutation or amplification of PI3K and AKT do not appear to occur and loss of PTEN seems to be infrequent in MM [60,89,90], the PI3K/AKT pathway has been reported to be aberrantly activated in this tumor. In particular, an elevated activity of AKT has been observed in more than two-thirds of MM tissues [60,91].…”
Section: Inhibition Of Intracellular Signaling Effectors: Targeting Tmentioning
confidence: 94%
“…In addition, high levels of activated AKT have been found in MM cell lines in association with a SV40-positive status and/or with activated signaling from several growth factor receptors, including those for HGF, VEGF, PDGF and EGF [20,57,66,92,93]. Furthermore, it has been demonstrated that AKT plays an important role in asbestos-induced mesothelial cell transformation and that inhibition of the PI3K/AKT pathway can induce growth arrest and apoptosis, reduce migration and invasion and sensitize MM cells to different anticancer agents [8,[90][91][92][93][94][95][96][97]. Collectively, these findings provide a strong rationale for targeting the PI3K/AKT signaling axis in MM patients.…”
Section: Inhibition Of Intracellular Signaling Effectors: Targeting Tmentioning
confidence: 96%